PENEGAKAN HUKUM TERHADAP PENGGUNAAN KEWENANGAN DISKRESI YANG BERIMPLIKASI TINDAK PIDANA KORUPSI - Muhammad Samsul Qamaruddin Bowta; Hufron Hufron (Gapenas Publisher, 2022)
The government has the power to intervene in all aspects of people's lives through public power, including areas not regulated by law. This condition then causes the state to need its own initiatives and policies. This is what is called the concept of discretion in administrative law. However, the exercise of discretion also tends to detect abuse and arbitrariness of duties, which can result in criminal acts of corruption as referred to in Article 3 of the Anti-Corruption Law. Because the discretionary authority is for the public interest or the public interest, then if the discretionary authority is used for purposes other than the public interest or the public interest, then the discretionary act becomes a criminal act of corruption in terms of crime. This could be considered the abuse of influential work.